(untitled) (Revista Contexto & Saúde, 2025)
To understand Collaborative Interprofessional Practice experiences from primary healthcare professionals’ and residents’ perspective. This qualitative study involved 12 healthcare professionals and residents, including residents with at least three months of service and professionals with more than six months of service. Data collection used semi-structured interviews, lasting an average of 25 minutes. After transcribing the recordings, the statements were organized into topics. It was revealed that understanding Collaborative Interprofessional Practice must be based on interactions with professionals to serve several areas of the healthcare universe. Service experiences and strengthening of the topic permeate numerous specific situations in the studied service, but the collaborative act strengthens care. Professionals and residents understand that Collaborative Interprofessional Practice is essential for strengthening healthcare.